Gang Membership and Gang Crime in New Zealand: A National Study Identifying Spatial Risk Factors - Breetzke, Gregory D. (Criminal justice and behavior, 2022)
In this exploratory study, we identify the spatial risk factors associated with gang membership and gang crime in New Zealand using social disorganization as a theoretical framework. Gang membership data from the Gang Intelligence Center and gang crime data from New Zealand Police are included in spatial regression models to identify risk factors. Overall marginal support was found for the use of social disorganization constructs to explain gang membership and gang crime in New Zealand. Higher deprivation and higher diversity were both found to be associated with gang membership and gang crime, respectively. Some similarities and notable differences were observed between our results and the mainly U.S.-centric results of past spatial gang research. This study allows for a greater understanding of the generalizability of the social disorganization theory to explain gang membership and gang crime in areas with markedly different cultural perspectives and ethnocentricities to the United States.